Oral health status and related risk factors among adolescents attending high schools in Khartoum, Sudan: A cross-sectional study - Hajir Omara; Amal Elamin (Elsevier, 2022)
Objectives: Effective dental services must be based on reliable evidence of oral diseases status and treatment needs. The aim of this study was to assess oral health status and associated risk factors among adolescents attending high school in Khartoum, Sudan. Methods: A school-based survey was conducted among 420 adolescents (13-18 years old). Participants completed a questionnaire about their socio-demographics and oral habits. They received clinical examination, assessing their oral health status using the World Health Organization (WHO) oral health survey for dentition and periodontal status; mean Decayed, Missing and Filled Teeth (DMFT), and Community Periodontal Index (CPI). Results: High dental caries prevalence of 91.1%, with mean DMFT of 3.3 (±1.8) and Significant Caries index (SIC) of 5.2 were found among the participants. Untreated decayed teeth dominated the DMFT scores (DT = 3.06 ± 1.7). The results of CPI depicted that 96% of participants had unhealthy periodontium, with majority of subjects (79.5%) having CPI maximum scores of 2. Increased age and being enrolled in a public school were the main risk factors associated with caries (p = 0.01). Increased CPI scores were found to be significantly higher among males (p = 0.006) and among public schools' attendees (p = 0.039). High maternal education was associated with participants' healthier periodontium (p < 0.01). Conclusions: Sudanese adolescents have high prevalence of caries and unhealthy periodontium, which imposes a need for preventive and treatment programs to improve their oral health status. The significant associations between participants' oral health status and their gender, school-type and age may suggest considering these when designing schools' oral health programs.